Teacher’s Strategies to Overcome Students’ Difficulties When Implementing Time Token Arends Method in Learning Speaking English - Nailul Fauziyah; Nurul Fitria (Journal of Advanced Multidisciplinary Research, 2021)
This study concerned with the teacher’s strategies in learning speaking English. This research is focused on how the teacher overcomes the students’ weaknesses in learning speaking English when implementing Time Token Arends method. By using a descriptive qualitative research within a teacher of MA Al-Bairuny as a subject of its research found that: (1) the student had difficulty in inhibition such as: difficulty in starting to speak because of being worried of making mistakes, difficulty in answering the question from the teacher, and they felt nervous and shy to speak in front of the class. (1) The teacher used “Look in the Face” strategy to overcome the difficulties; (2) the teacher used “Communication” strategies to overcome the students’ difficulties in nothing to say, such as: students had no idea to speak, student got difficulty to express what he wanted to speak, and student had no bravery to express their thought; (3) the teacher used “Interdependence” strategies to overcome the students’ difficulties in un-event participant; (4) the teacher used “Responsibility” strategies to overcome students’ difficulties in mother tongue used, such as: students felt easier for communication each other using Java Language, so they ignored the teacher’s instruction for speaking English; (5) then, after the learning process, teacher made a schedule for this group to evaluate their teamwork process in order to give them motivation and evaluation. Thus, the students’ improvement on their speaking skill has been the aim of the research.